Indonesian shrimp resource accounting for sustainable stock management - ZUZY ANNA (Society for Indonesian Biodiversity, 2017)
Abstract. Anna Z. 2017. Indonesian shrimp resource accounting for sustainable stock management. Biodiversitas 18: 248-256. Shrimp fisheries is a resource of important economic value, and is one of the high-demand commodities. Although regarded as a resource that has the ability to grow relatively quick and allows for a year-round production, these resources could experience declining production, or even extinction, if not managed properly. Planning the management of shrimp fishery stock requires basic information on the stock dynamics, both in terms of its natural production and utilization, through resource accounting, mandated by the Agenda 21 of United Nation Conference on Environment and Development (UNCED), formulated in the System of Integrated Environmental and Economic Accounting (SEEA). This study measures the accounting of the shrimp resources, both physical and monetary. In addition, the study also aims to measure the shrimp resource that can be utilized (fishable biomass), from the balance of resources. The approach used in this study is a standard bioeconomic model, with Fox model to estimate biological parameters, and methods of System of National Accounts of FAO (2004), named recursive model, adapted to the existing data. The results of the analysis, includes the calculation of standing stocks (physical asset account), fishable biomass, depletion, as well as monetary accounts. Result shows that the overall condition of the stock still in surplus, where the standing stocks from 1988 to 2014, are in the range of 200,000 to 900,000 tons yearly, with the monetary value between IDR 500 billion to 2 trillion. The intrinsic growth of shrimp tend to be positive in average, with values in the range of -258,000 tons to 263,890 tons. The trend estimation for the next five years (2015-2020), showed a decrease in the stock, and the stock closed as many as 350,000 tons in 2020. This paper also suggests the policy recommendations for the development and management of shrimp resources, in Indonesia. Keywords: Bio-economic modelling, fishery accounting, fishery stock management plan, monetary account, physical account, shrimp